2011
DOI: 10.1123/jpah.8.s2.s151
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Observed Park Physical Activity Intensity Level by Gender, Race, and Age: Individual and Joint Effects

Abstract: Observations revealed significant differences in intensity levels across gender, age, and race groups. Future interventions should emphasize park design that promotes increased MVPA among diverse groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 57 publications
5
70
4
Order By: Relevance
“…Although parks have been shown to be important environments for physical activity [7,8,71,72], opportunities to improve physical activity in park settings exist [73,74]. As more than 20 % of the respondents in this study engage in no physical activity and more than 60 % were either overweight or obese, there is a need to increase physical activity participation among residents which can subsequently improve health.…”
Section: Discussionmentioning
confidence: 95%
“…Although parks have been shown to be important environments for physical activity [7,8,71,72], opportunities to improve physical activity in park settings exist [73,74]. As more than 20 % of the respondents in this study engage in no physical activity and more than 60 % were either overweight or obese, there is a need to increase physical activity participation among residents which can subsequently improve health.…”
Section: Discussionmentioning
confidence: 95%
“…27,29 There also appears to be age, sex and racial differences regarding PA patterns in public parks. 29,30 Perceived neighborhood quality and safety are also important factors for using public parks to engage in PA, although more work is needed in this area to understand these complex social interactions. 24 Recently, outdoor fitness equipment spaces have emerged in public parks to promote active options, although there currently is mixed evidence with respect to the impact of the recreational environment model on increasing PA patterns.…”
Section: Public Parks and Healthy Living -State Of Current Evidencementioning
confidence: 99%
“…The built features of parks such as playgrounds, sports fields, tennis and basketball courts, and, in particular, walking trails have been shown to affect physical activity across the life span (12)(13)(14)(15)(16)(17)(18)(19). Parks in lower-income areas have been shown to have fewer built features (12)(13)(14)23,24) and fewer users (23,24) than those in higher-income areas. Most park studies have focused on a specific population within a small geographic area and have been of short duration.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using SOPARC have documented the characteristics of parks (accessibility, usability, and whether or not they provide supervision, equipment, and organized activities) and park users (levels and types of physical activity, sex, race/ethnicity, and age group) (12,13,15,18,20). These studies consistently report that most park users (>60%) are male and sedentary when observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation